2013
DOI: 10.2460/ajvr.74.1.90
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding a selected combination of galacto-oligosaccharides and a strain of Bifidobacterium pseudocatenulatum on the intestinal microbiota of cats

Abstract: Results suggested that feeding 1% GOS-BP-B82 combination had some positive effects on the intestinal microbiota in cats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 34 publications
1
26
0
Order By: Relevance
“…with the use of 1% of MOS in dogs; Biagi et al. () found that feeding cats a combination of 1% of galacto‐oligosaccharides (GOS) and Bifidobacterium pseudocatenulatum increased bifidobacteria after 16 days; Kanakupt, Vester Boler, Dunsford, and Fahey () also detected an increase in Bifidobacterium spp. with 0.5% supplementation of FOS, GOS or both in cats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…with the use of 1% of MOS in dogs; Biagi et al. () found that feeding cats a combination of 1% of galacto‐oligosaccharides (GOS) and Bifidobacterium pseudocatenulatum increased bifidobacteria after 16 days; Kanakupt, Vester Boler, Dunsford, and Fahey () also detected an increase in Bifidobacterium spp. with 0.5% supplementation of FOS, GOS or both in cats.…”
Section: Discussionmentioning
confidence: 99%
“…with the use of 1% of MOS in dogs; Biagi et al (2013) found that feeding cats a combination of 1% of galacto-oligosaccharides (GOS)…”
Section: Discussionmentioning
confidence: 99%
“…Differences in results might be explained by differences in the levels of supplementation among studies: for example, up to 9·0 % as fed oligofructose in Hesta et al (60) ; maximum 0·6 % DM MOS in Aquino et al (62) ; 1 % synbiotic in Biagi et al (53) .…”
Section: In Vivo Studiesmentioning
confidence: 96%
“…A more recent study demonstrated the positive effect of prebiotic use in cats (Biagi et al . ). Synbiotics refer to nutritional supplements combining probiotics and prebiotics for a synergistic effect (Serban ).…”
Section: Therapeutic Targetsmentioning
confidence: 99%
“…2000 ). A more recent study demonstrated the positive effect of prebiotic use in cats (Biagi et al . 2013 ).…”
Section: Antibiotics and Gastroprotectantsmentioning
confidence: 99%